THE IMAGE OF A TEACHER FROM THE LENS OF STUDENT TEACHERS - Teresita Dinoc Ignacio; Colette Angel Lydio (Erudio Journal of Educational Innovation, 2021)
This qualitative-descriptive study aims to find the image of a teacher ascribed by student teachers who were in the terminal phase of their teacher education training.  All the 217 student teachers for elementary and secondary education of a university for AY 2017-2018 were tasked to write an essay as to what is the image of a teacher.  Content analysis was applied manually to the essays to generate the feature in focus.  Seven themes emerged as the top images, namely: knowledge provider/facilitator, parent, catalyst, hero/superhero, role model, friend, and jack of all trades. It is promising that the images identified by these student teachers are mostly positive and aligned with the qualities of a 21st century teacher.